The whole story: a systematic review of economic evaluations of HPV vaccination including non-cervical HPV-associated diseases - Anita W. M. Suijkerbuijk; Robine Donken; Anna K. Lugnér; G. Ardine de Wit; Chris J. L. M. Meijer; Hester E. de Melker; Johannes A. Bogaards (Expert Review of Vaccines, 2017)
Introduction: Many economic evaluations of HPV vaccination have been published, but most have focused on the prevention of cervical disease as a primary health outcome. The cost-effectiveness of vaccination is likely to be underestimated if not all HPV-associated diseases are taken into account. In this review, we assess the influence of non-cervical HPV-associated diseases on the incremental cost-effectiveness ratio (ICER) of preadolescent HPV vaccination. Areas covered: We systematically searched the literature and identified 18 studies that included non-cervical diseases in the estimates of cost-effectiveness of HPV-vaccination. When taking other HPV-related diseases into account compared to not including such other diseases, the mean ICERs were 2.85 times more favorable for girls only vaccination and 3.89 times for gender neutral vaccination. Expert commentary: Including non-cervical diseases in economic evaluations of HPV vaccination programs makes it more likely that the ICER falls beneath accepted cost-effectiveness thresholds and therefore increases the scope for gender neutral vaccination.